It's <span>extraneous. I know this because it leads to a straight answer. </span> <span><span><span><span>3x</span>+5</span>+<span>15</span></span>=<span><span>2x</span>+5</span></span><span><span><span><span> 26x</span>+15</span><span>5x</span></span>=<span><span>2x</span>+5</span></span> <span><span><span>26x</span>+15</span>=<span><span>10<span>x2</span></span>+<span>25x</span></span></span><span><span><span><span> 26x</span>+15</span>−<span>(<span><span>10<span>x2</span></span>+<span>25x</span></span>)</span></span>=<span><span><span>10<span>x2</span></span>+<span>25x</span></span>−<span>(<span><span>10<span>x2</span></span>+<span>25x</span></span>) </span></span></span> −10x2+x+15=0<span> x=<span><span><span>−b</span>±<span>√<span><span>b2</span>−<span><span>4a</span>c</span></span></span></span><span>2a</span></span></span><span> x=<span><span><span>−<span>(1)</span></span>±<span>√<span><span><span>(1)</span>2</span>−<span><span>4<span>(<span>−10</span>)</span></span><span>(15)</span></span></span></span></span><span>2<span>(<span>−10</span>)</span></span></span></span><span> x=<span><span><span>−1</span>±<span>√601</span></span><span>−20</span></span></span><span><span> x=<span><span>120</span>+<span><span><span><span><span>−1</span>20</span><span>√601</span></span><span> or </span></span>x</span></span></span>=<span><span>120</span>+<span><span>120</span><span>√601</span></span></span></span><span> x=<span><span>120</span>+<span><span><span>−1</span>20</span><span>√601 </span></span></span></span><span> x=<span><span>120</span>+<span><span>120</span><span>√601</span></span></span></span> <span><span>x=<span><span>120</span>+<span><span><span><span><span>−1</span>20</span><span>√601</span></span><span> or </span></span>x</span></span></span>=<span><span>120</span>+<span><span>120</span><span>√<span>601
Hoped I helped!</span></span></span></span></span>